Comparative study of carbide slag autoclaved aerated concrete (AAC) manufactured under thermal oven and microwave pre-curing process: Foaming course, rough body strength and physic-mechanical properties. (10th March 2020) - Cai, Lixiong; Tang, Tao; Liu, Miao; Xie, Dingkun
Highlights: Introducing microwave heating technology in pre-curing stage of carbide slag AAC preparation. Measuring microwave pre-curing AAC slurry gas foaming height with laser ranging method. Detecting rough body strength with thrust and tensile force tester to measure the curing effect. Abstract: The substitution of carbide slag to quicklime in carbide slag autoclaved aerated concrete (AAC) preparation caused significant side-effect on stable formation of porosity structure in pre-curing process. With objective of regulating slurry foaming course and rough body strength development during pre-curing process of carbide slag AAC production, microwave heating technology was introduced to control the slurry temperature accurately, and regulate the foaming and thickening process ulteriorly. Therefore, the discrepancy between conventional and microwave pre-curing process in mould and energy were discussed qualitatively. Moreover, to figure out the superiority and effect law of microwave pre-curing process with different curing temperature, the comparison between conventional and microwave pre-curing process on slurry foaming course, rough body development and physic-mechanical properties were investigated. The discrepancy analysis illuminated that with transition from thermal oven curing to microwave pre-curing, mixing water and mould should be changed from warm water (＞50 °C) and metal mould to normal temperature water and microwave penetrable mould respectively, meanwhile, the theoretical energy requirement was significantly reduced. Otherwise, the experimental results indicated that microwave pre-curing technology effectively accelerate the gas foaming rate in early stage and increased ultimate foaming ratio with increasing of curing temperature. However, the gradient temperature of microwave pre-curing between foaming and thickening stage should not exceed 20 °C, so as to avoid the temperature stress on bonding surface of rough body and container, which may cause ring collapse. Moreover, rough body strength development was improved with utilizing of microwave pre-curing technology, the pre-curing duration could be shortened by 0.5–1 h relative to thermal oven pre-curing process. Furthermore, the physic-mechanical performance of thermal oven and microwave pre-cured carbide slag AAC specimens were comparable. Overall, the results indicated that microwave pre-curing technology has great potential to be an alternative curing method for manufacturing carbide slag AAC.